THE IMPORTANCE OF ENGLISH LANGUAGE FOR CAREER OPPORTUNITIES IN THE ASEAN - Mbuh, Khan Eric (PEOPLE: International Journal of Social Sciences, 2015)
This article presents the reasons why ASEAN students must study English Language in order to be better placed in the ASEAN job market. Another preoccupation of the article is to define and understand what the words career and English for career means. The article also includes a proposed syllabus for career English. That is the various topics that teachers should teach students in other to prepare them for the ASEAN job market. In order words, the proposed syllabus is based on English for communication at the workplace. However, no matter how intelligent and knowledgeable a teacher is, if he or she has no grasp of good teaching techniques or methods, it will be difficult to transmit knowledge to the students. As a result, this article also examines some teaching method that ESL (English as Second Language Teachers) should adopt in order for students to be able to grasp the four language skills which are listening, speaking, reading and writing.